2017
DOI: 10.1186/s13045-016-0381-z
|View full text |Cite
|
Sign up to set email alerts
|

Is CD47 an innate immune checkpoint for tumor evasion?

Abstract: Cluster of differentiation 47 (CD47) (also known as integrin-associated protein) is a ubiquitously expressed glycoprotein of the immunoglobulin superfamily that plays a critical role in self-recognition. Various solid and hematologic cancers exploit CD47 expression in order to evade immunological eradication, and its overexpression is clinically correlated with poor prognoses. One essential mechanism behind CD47-mediated immune evasion is that it can interact with signal regulatory protein-alpha (SIRPα) expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 48 publications
2
124
0
Order By: Relevance
“…CD47 is recognized as a checkpoint for the innate immune response and delivers an inhibitory signal when it binds with SIRPα expressed on phagocytes (30)(31)(32). Anti-CD47 treat-30-32).…”
Section: Discussionmentioning
confidence: 99%
“…CD47 is recognized as a checkpoint for the innate immune response and delivers an inhibitory signal when it binds with SIRPα expressed on phagocytes (30)(31)(32). Anti-CD47 treat-30-32).…”
Section: Discussionmentioning
confidence: 99%
“…At least three CD47 antagonists (Hu5F9-G4, CC-90002, and TTI-621) ( Table 1) are currently in active phase I clinical trials, covering hematological malignancies and solid tumors (4). With the release of their safety profiles (5-7), more attention is now being focused on comparing the side effects (8) and efficacies of these inhibitory reagents.…”
Section: Perspectivementioning
confidence: 99%
“…Accumulating evidence has suggested that the TSP‐1/CD47 axis could be a promising therapeutic target in cancer as well as in cardiovascular diseases . Besides its well‐established anti‐angiogenic and anti‐proliferative effects when engaged with TSP‐1, CD47 also participates in immune suppression of macrophages and is found widely overexpressed in different types of cancer . As a self‐recognition signal, CD47 on cancer cells associates with SIRPα (signal regulatory protein alpha) on macrophages and inhibits phagocytic activities.…”
Section: Conclusion and Future Considerationsmentioning
confidence: 99%
“…CD47 also participates in immune suppression of macrophages and is found widely overexpressed in different types of cancer. 122 As a selfrecognition signal, CD47 on cancer cells associates with SIRPa (signal regulatory protein alpha) on macrophages and inhibits phagocytic activities. Interestingly, TSP-1 also interacts with SIRPa expressed on non-phagocytic cells; however, the potential role of how TSP-1 modulates the CD47/SIRPa axis during macrophage activation remains unclear.…”
Section: Correlations Between Tsp-1 and Vegfmentioning
confidence: 99%